2018
DOI: 10.3390/molecules23061274
|View full text |Cite
|
Sign up to set email alerts
|

Betaine Attenuates Monocrotaline-Induced Pulmonary Arterial Hypertension in Rats via Inhibiting Inflammatory Response

Abstract: Background: Pulmonary arterial hypertension (PAH) is characterized by increased pulmonary vascular resistance, leading to right ventricular failure and death. Recent studies have suggested that chronic inflammatory processes are involved in the pathogenesis of PAH. Several studies have demonstrated that betaine possesses outstanding anti-inflammatory effects. However, whether betaine exerts protective effects on PAH by inhibiting inflammatory responses in the lungs needs to be explored. To test our hypothesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 59 publications
1
40
0
Order By: Relevance
“…Because of the hydrophobicity of the 3 methyl groups and hydrophilicity of the carboxyl, a tight protective membrane could be formed around cells to prevent from oxidative stress and cell damage . The results are in line with previous findings that betaine prevents oxidative stress, inhibits apoptosis, and possesses antiinflammatory effects …”
Section: Discussionsupporting
confidence: 91%
“…Because of the hydrophobicity of the 3 methyl groups and hydrophilicity of the carboxyl, a tight protective membrane could be formed around cells to prevent from oxidative stress and cell damage . The results are in line with previous findings that betaine prevents oxidative stress, inhibits apoptosis, and possesses antiinflammatory effects …”
Section: Discussionsupporting
confidence: 91%
“…Zhao et al reported that the NF‐κB pathway may contribute to candesartan‐induced initiation and progression of PIH 36 . Furthermore, betaine treatment has been shown to attenuate pulmonary arterial hypertension through the inhibition of inflammatory response by inactivating the NF‐κB pathway 37 . Impairment of ET‐1 by suppression of ETAR deactivates the NF‐κB pathway, supporting the implication of mediation of the ET‐1 axis in neuropathic pain 38 .…”
Section: Discussionmentioning
confidence: 93%
“…There are lots of credibility evidences show that betaine also have the function of anti-inflammation and improving intestinal barrier function [23] . Yang et al found that betaine alleviates monocrotaline-induced pulmonary hypertension in rat by restraining the inflammatory response, such as down-regulating the NF-κB signaling pathway or inhibiting the inflammatory reaction [24] . Olli.…”
Section: Discussionmentioning
confidence: 99%